Kitāb al-Ḥujjah ʿAlā Ahl al-Madīnah and the Transition from Regional Schools to Personal - Melchert, Christopher ca. 20./21. Jh. (Studia Islamica, 2022)
K. al-Ḥujjah ʿalā ahl al-Madīnah by Muḥammad ibn al-Ḥasan al-Shaybānī (d. 189/804-5) is a witness to the state of the regional school of Medina before it had been absorbed by (survived only in) the Mālikī personal school. Schacht asserts that each regional school had its characteristic authorities among the Followers, and the Ḥujjah confirms that, sometimes appealing to Kufan Followers against Medinese, sometimes complaining that the Medinese are not staying loyal to their own Medinese Followers. Sometimes also the Ḥujjah testifies to Mālik’s pre-eminence among the Medinese of his time, sometimes by appealing to him as ‘your faqīh’, with whom the Medinese ought to agree but do not, but mainly as their pre-eminent traditionist. Schacht observed that Shaybānī adduced hadith more often than Abū Yūsuf, and the Ḥujjah often adduces hadith in its arguments against the Medinese. Most often, however, it adduces logical consistency against Medinese positions. Altogether, it suggests that personal schools evolved out of regional by accentuation of the personal element already present in the tradition of regional authorities. By adducing hadith from a wider range of authorities than the Muwaṭṭaʾ, it implicitly argues that Ḥanafi law is superior because it represents the jurisprudence of the whole Empire, not just one centre.